Pemahaman Konsep dan Kesulitan Siswa SMA pada Materi Hukum Newton - Ayu Lingga Ratna Sari; Parno Parno; Ahmad Taufiq (Pascasarjana Universitas Negeri Malang, 2018)
Abstract: This study was purposed to determine the mastery and difficulty concepts of Senior High School students in Newton's law. The study was employed a descriptive analysis to find the mastery and difficulty concepts of  34 students of senior high school class X-MIPA of SMA Negeri 1 Kandangan Kediri. The reasoning multiple choice (two-tier) using instrumental test of mastery concept was used with reliability value of 0.649. The result of the analysis presented that the mean value of student's concept mastery in Newton's law was of 24.3 with a maximum value of 100 presenting a low category. The low score of student's understanding exhibited that students had difficulties in Newton's law concept. In general, many students had difficulties in identifying and interpreting the formula , identifying the forces with free body diagram, and understanding action, and reaction forces. Abstrak: Penelitian ini bertujuan untuk mengetahui pemahaman konsep dan kesulitan siswa SMA pada materi hukum Newton. Penelitian ini merupakan penelitian deskriptif untuk menemukan pemahaman konsep dan kesulitan pada 34 siswa X-IPA SMA Negeri 1 Kandangan Kediri, menggunakan instrumen tes pemahaman konsep berupa pilihan ganda beralasan dengan nilai reliabilitas 0,649. Hasil analisis menunjukkan nilai rata-rata pemahaman konsep siswa pada materi hukum Newton sebesar 24,3 dari nilai maksimum 100, berada dalam kategori rendah. Hal ini menunjukkan bahwa siswa mengalami kesulitan dalam materi hukum Newton. Secara umum, siswa mengalami kesulitan mendefinisikan dan memahami rumusan , mengidentifikasi gaya menggunakan diagram benda bebas, dan memahami gaya aksi dan reaksi.